2012
DOI: 10.1007/s00595-012-0304-8
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment for isolated superior mesenteric artery dissection

Abstract: We recommend conservative treatment as the first choice for isolated SMA dissection, even if the patient has abdominal pain and tenderness, given that there are no signs of peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…The indications for surgical treatment are arterial rupture, aneurismal dilation (>2 cm in diameter), bowel infarction, a positive peritoneal irritation sign, and progressive or persistent abdominal pain despite conservative treatment [ 2 , 4 , 9 , 15 ]. However, there are controversies in the treatment strategy for patients with persistent abdominal pain despite conservative management and complete obstruction due to thrombosis or stenosis of the SMA true lumen [ 12 , 15 , 25 , 26 , 28 , 29 ]. Causes of failure in conservative treatment include persistent abdominal pain, the development of aneurismal enlargement, a ruptured SMA aneurysm, and evidence of bowel ischemia or infarction [ 4 , 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The indications for surgical treatment are arterial rupture, aneurismal dilation (>2 cm in diameter), bowel infarction, a positive peritoneal irritation sign, and progressive or persistent abdominal pain despite conservative treatment [ 2 , 4 , 9 , 15 ]. However, there are controversies in the treatment strategy for patients with persistent abdominal pain despite conservative management and complete obstruction due to thrombosis or stenosis of the SMA true lumen [ 12 , 15 , 25 , 26 , 28 , 29 ]. Causes of failure in conservative treatment include persistent abdominal pain, the development of aneurismal enlargement, a ruptured SMA aneurysm, and evidence of bowel ischemia or infarction [ 4 , 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, recent first-line therapy has been conservative management, with or without antithrombotic treatment with antiplatelet and anticoagulant therapy to prevent TL occlusion by stabilizing the intimal flap (Figure, Table). [3][4][5][6][7][8][9][10][11] For a subset of patients with persistent symptoms because of critical bowel ischemia or infarction caused by compression of the TL of the SMA or rupture of the dissecting SMA, endovascular treatment (EVT) with stents or open surgical repair (OSR) is indicated without delay. 11 In the current shift towards EVT for aortic or peripheral arterial lesions, 12 EVT predominates.…”
Section: Ogino Hmentioning
confidence: 99%
“…In general, some combination of antihypertensive, anticoagulation, or antiplatelet drug therapy is recommended. 16 Many authors reported good outcomes using anticoagulation therapy, 9,17 and some have called for anticoagulation as first-line therapy. 18 We found that in symptomatic patients without evidence of ischemia, there was no significant difference in occurrence of LVT or aneurysm in patients treated with medical management vs observation alone.…”
Section: Discussionmentioning
confidence: 99%